Geochemical and paleontological evidence of early Cambrian dynamic ocean oxygenation and its implications for organic matter accumulation in mudrocks at the Three Gorges area, South China. (December 2022) - Zhang, Yu; Zhang, Tongwei; Huang, Dejiang; Shao, Deyong; Luo, Huan
Abstract: The evolution of global ocean oxygenation during the early Cambrian remains highly controversial, making it difficult to evaluate how environmental triggers play a role in controlling the organic matter (OM) accumulation in black shales. In this study, an integrated approach, including total organic carbon (TOC) content, major and trace element geochemistry, and microscope images, was systematically conducted in a continuous core well that penetrated through the Lower Cambrian Yanjiahe (YJH)–Shuijingtuo (SJT, subdivided into SM Ⅰ, SM Ⅱ, SM Ⅲ, and SM Ⅳ members) successions (∼541-514Ma) at the Three Gorges area, Yangtze Platform, South China. Our results showed that the ocean stepwise oxidation evolution in shelf-slope environments occurred even though the marine redox state showed highly dynamic fluctuations during the early Cambrian. Based on geochemical proxies and sedimentological and faunal criteria, the OM-rich mudrocks in the SJT Formation can be divided into two units. The lower part (SM Ⅰ) contains a higher TOC content (average value 5.71 wt%) than the upper part (SM II, average TOC value of 2.73 wt%). SM Ⅰ are characterized by high MoEF, UEF, Corg /P, and U/Th ratios, indicating that SM I was deposited under constantly euxinic conditions. The relatively declining MoEF, UEF, Corg /P, and U/Th ratios at the transition interval between the SM Ⅰ and SM II records a change in bottom-water to predominantly anoxic conditions with intermittent oxygenation. Correspondingly, the biological record evolved from extremely limited benthic organisms to diverse sponge spicules. The high paleoproductivity, sustained euxinic conditions, and limited dilution linked to sea-level rising are responsible for the OM enrichment in SM I black shales. In comparison, SM II was deposited under mainly suboxic/dysoxic conditions with the lower Corg /P, U/Th ratios, and moderate enrichment of Mo (<25 ppm), which were accompanied by the abundant development of agglutinated benthic foraminifera, sponge spicules, radiolarians, etc. The OM accumulated under low-oxygen conditions and increased terrigenous input even though the paleoproductivity remained at a high level during the deposition of SM Ⅱ. The ocean bottom-water then evolved into oxic conditions with extremely low Corg /P, U/Th ratios, and no Mo concentrations in OM-lean calcareous mudrocks and limestone developed in the upper part of the SJT Formation, including SM Ⅲ (avg. TOC is 0.6 wt%) and SM Ⅳ (avg. TOC is 0.09 wt%). The combination of an oxic depositional environment, limited primary productivity, and dilution of terrigenous inputs was unfavorable for OM enrichment during that period. Highlights: The ocean stepwise oxidation evolution occurred during the early Cambrian. The discovery of agglutinated foraminifera constrains the ocean redox conditions. The organic-rich layers divided into two members were deposited under distinct redox state. The redox state and terrigenous flux control the OM enrichment under high paleoproductivity.